Tropical and Subtropical Fruits in India - Mitra, Sisir (Department of Agronomy and Horticulture, IPB University, 2014)
India is the second largest producer of fruits in the world with an annual production of 81.2 million tonnes contributing 12.6% of world fruit production next only to China (21.2%). Of late, with growing population and realization of commercial and nutritional values, the demand and requirement for fruits has increased manifold globally and so is in India. Since then, India has managed a steady growth in area expansion and production of fruits. Even in 2012-2013, increase in area and production of fruits in India was 4.1 and 6.4 times over 2011-2012 Of these, tropical and subtropical fruits contribute a major share, and the important fruits are mango, banana, papaya, citrus, guava, pineapple, litchi, sapota and pomegranate. Among the minor fruits (less area in cultivation than the major fruits) are jackfruit, bael, aonla, carambola, syzygiums, passion fruit and tamarind are also growing in many states of India.